2022
DOI: 10.1021/acsaem.1c03721
|View full text |Cite
|
Sign up to set email alerts
|

Charge Separation by Imidazole and Sulfonic Acid-Functionalized Covalent Organic Frameworks for Enhanced Proton Conductivity

Abstract: The ion aggregation induced by a strong Coulomb force leads to hard charge separation and poor proton conductivity. Herein, covalent organic frameworks (COFs) linking both positive charged imidazole and negative charged sulfonic acid were produced and were finally incorporated with NH4Br molecules. As a result, the charge separation ability of NH4Br molecules is profoundly enhanced by charged groups on COFs, which is proved by X-ray photoelectron spectroscopy measurement. The proton conductivity of charged COF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…NH4Br@COF-Im + À SO 3À 3.69×10 À 3 90 °C and 100 % RH [55] Im@XJCOF-1 4.38×10 À 2 140 °C and anhydrous [56] PA@EB-COF 2.77×10 À 2 180 °C and anhydrous [57] Im@TPB-DMTP-COF 4.37×10 À 3 130 °C and anhydrous [43] Im@Py-TT-COF-50 3.08×10 À 3 130 °C and anhydrous [49] Im@Py-BT-COF-50 2.92×10 À 3 130 °C and anhydrous [49] Im@Tp-DADMB 2.4×10 À 3 130 °C and anhydrous [58] Im@UIO-67 1.44×10 À 3 120 °C and anhydrous [59] Trz@TPB-DMTP-COF 1.10×10 À 3 130 °C and anhydrous [43] Im@Py-BD-COF-50 8.20×10 À 4 130 °C and anhydrous [49] Im@Py-TT-COF-30 5.11×10 À 4 130 °C and anhydrous [49] Im@Py-BT-COF-30 4.23×10 À 4 130 °C and anhydrous [49] Im@Py-BD-COF-30 5.85×10 À 5 130 °C and anhydrous [49] Im@TPB-TP-COF 4.71×10 À 7 120 °C and anhydrous [43] gradient with imidazole or water molecules as carriers.…”
Section: Compoundmentioning
confidence: 99%
“…NH4Br@COF-Im + À SO 3À 3.69×10 À 3 90 °C and 100 % RH [55] Im@XJCOF-1 4.38×10 À 2 140 °C and anhydrous [56] PA@EB-COF 2.77×10 À 2 180 °C and anhydrous [57] Im@TPB-DMTP-COF 4.37×10 À 3 130 °C and anhydrous [43] Im@Py-TT-COF-50 3.08×10 À 3 130 °C and anhydrous [49] Im@Py-BT-COF-50 2.92×10 À 3 130 °C and anhydrous [49] Im@Tp-DADMB 2.4×10 À 3 130 °C and anhydrous [58] Im@UIO-67 1.44×10 À 3 120 °C and anhydrous [59] Trz@TPB-DMTP-COF 1.10×10 À 3 130 °C and anhydrous [43] Im@Py-BD-COF-50 8.20×10 À 4 130 °C and anhydrous [49] Im@Py-TT-COF-30 5.11×10 À 4 130 °C and anhydrous [49] Im@Py-BT-COF-30 4.23×10 À 4 130 °C and anhydrous [49] Im@Py-BD-COF-30 5.85×10 À 5 130 °C and anhydrous [49] Im@TPB-TP-COF 4.71×10 À 7 120 °C and anhydrous [43] gradient with imidazole or water molecules as carriers.…”
Section: Compoundmentioning
confidence: 99%
“…COF-PI-1 was prepared from amino-substituted porphyrin 5,10,15,20-tetrakis(4-aminophenyl) porphyrin (Tph), imidazolium-IL-attached styrene 3-methyl-1-(4-vinylbenzyl)-benzimidazolium bromide (Bim-Br), and Dha, and then COF-PI-2 was obtained via the post-synthetic metallization of the porphyrin entity by Co(OAc) 2 in COF-PI-1. Wang, Xu, and Zhang et al [ 84 ] synthesized a hydrazone-linked ILCOF, COF-Im + -SO 3 – , from 1,3-propane sultone and COF-Im, which was prepared from 1,3,5-trisformylbenzene and 2,5-bis(3-(1H-imidazole-1-yl) propoxy)terephthalohydrazide. Wang and Wang et al [ 85 ] reported two imidazolium ILCOFs (COF-HNU3 and COF-HNU4) via the Williamson reaction of 1-(3-bromopropyl)-3-methyl-1H-imidazol-3-ium bromide or 1-(3-bromopropyl)-4-chlorine-3-methyl-1H-imidazol-3-ium bromide with COF-HNU2, which was synthesized by the Schiff reaction of 2-hydroxybenzene-1,4-dialdehyde and TAPB.…”
Section: Classification Structures and Synthesis Of Ilcofsmentioning
confidence: 99%
“…Additionally, sulfonic acid groups on SPEEK and imidazole groups on cross-linked poly­(1-vinyl imidazole) (CL-PVIMI) form acid–base pairs, which can generate ample interfacial channels and long-range proton-transport routes for PEMs. , Besides, the carboxylic (−COOH) groups in MOF-808 have inherently high hydration energy, and this increased water affinity also contributes to the process. The proton donor (acid group) and proton acceptor (base group) are in close proximity in the originated acid–base pairs in these membranes.…”
Section: Introductionmentioning
confidence: 99%